As disposições pedagógicas em cursos de formação inicial e continuada: um estudo de caso sobre o projeto primeiro passo – jovem aprendiz - Lima, Leonardo Araújo; Frota, Francisco Horácio Frota da Silva (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
The demand for skilled labor in productive activities and service demarcate professional education as an economic and social development strategy for the brazilian state This article discusses the pedagogical perspectives of public policies of education, specifically those policies at the level of initial and continuing training of workers. We propose to address this issue through conceptual review of the liberal foundations of education for work, and contextual and empirical analysis . For the latter chose a case study by the Projeto Primeiro Passo – Jovem Aprendiz, a vocational action of the government of the state of Ceará.